PRECONDITIONS FOR MANIFESTATION OF MUSIC TEACHERS’ PROFESSIONAL TYPES IN THE CONTEXT OF OCCUPATIONAL STRESS - STRAKŠIENĖ, Diana; URNIEŽIUS, Rytis (Studia Universitatis Babes-Bolyai Musica, 2019)
The article deals with the relation between professional types of music teachers and occupational stress manifesting itself in teachers’ professional activities. Various sources confirm that due to the specificity of music teachers’ profession, music teachers experience more stress at work compared with the teachers of other specialties. However, it is likely that stress affects different teachers to a different extent. The research results presented in this article are based on the data of the empirical research. Employing cluster analysis, the typology of music teachers according to their attitude towards the music teacher’s profession was established. The research revealed that music teachers could be characterised by different professional attitudes. Data analysis enabled to disclose three types of music teachers. The research confirmed that belonging to a particular type influenced manifestation of occupational stress in music teachers’ professional activities.